Dating deal with the Italian - Blake, Ally (Harlequin romance, 2025)
Band manager Sutton has heard her parents' love story hundreds of times. Only, when she arrives at the bar where her later mother first met her father, instead of finding her own love story, she's greeted by the world's grumpiest bartender: Dante. His past wounds run so deep that a romance with Dante simply isn't in the cards ... Though that doesn't mean sunshine-personified Sutton can't still persuade him to create a singles' night at his bar! But while they're busy bringing couples together, will they be able to stay away from their irrefutable chemistry?